Pengaruh Model Pembelajaran Role Playing terhadap Keterampilan Berbicara Siswa Kelas 2 SDN Kalisalam 2 pada Pembelajaran Bahasa Indonesia - Ika Nur Aini; Ludfi Arya Wardana; Didit Yuliankasdriyanto (Journal on Education, 2024)
This study aims to determine the comparison of students' speaking skills through pretest and posttest. Role Playing Learning Model is a student-centered, innovative learning model, positioning the teacher as an effective facilitator in contextual learning related to real life situations. This research used one group pretest-posttest design through purposive sampling. The data collection technique used was a test. The instrument used to collect data was a multiple choice test. Data analysis was conducted using the Paired Sample T-test. The results of data calculation through the Paired-Sample T-Test test obtained a significance level of 0.000, meaning that students' speaking skills are better after learning through the role playing learning model than before students receive learning. This means that the learning model has more influence on students' numeracy skills.